OFFSET
1,4
COMMENTS
If A(0, x) = x, A(n+1, x) = A( A(n, x)) = A(n, A(x)). Then A(n, x) = x + n*x^2 + n^2*x^3 + (n^3 + 2*n)*x^4 + (n^4 + 6*n^2)*x^5 + ... where [x^4] A(n, x) = A054602(n). - Michael Somos, Jan 22 2012
FORMULA
G.f. satisfies: A(-A(-x)) = x ; Also: A(x) = x + A(A(x))*series_reversion(A(x)).
Since g.f. satisfies: A(A(x)) = ( x - A(x) )/A(-x), then higher order self-compositions of A(x) reduce into expressions involving A(x) and A(-x). - Paul D. Hanna, Jul 22 2006
EXAMPLE
A(x) = x + x^2 + x^3 + 3x^4 + 7x^5 + 33x^6 + 109x^7 + 643x^8 +...
A(A(x)) = x + 2x^2 + 4x^3 + 12x^4 + 40x^5 + 168x^6 + 736x^7 + 3784x^8+..
x*A(A(A(x))) = x^2 + 3x^3 + 9x^4 + 33x^5 + 135x^6 + 627x^7 + 3141x^8+...
PROG
(PARI) {a(n)=local(A=x+x^2+x*O(x^n)); if(n<1, 0, for(i=1, n, A=x-subst(A, x, -x)*subst(A, x, A)); polcoeff(A, n))}
CROSSREFS
KEYWORD
nonn
AUTHOR
Paul D. Hanna, Jun 14 2006
STATUS
approved